Linguagem, poema e indizível: grafismos de uma poética em Fiama Hasse Pais Brandão - Borges, Alexander Jeferson Nassau (2014)
The corpus of this thesis is Obra breve, the poetic reunion of Portuguese author Fiama Hasse Pais Brandão (1938-2007), and its theme is the conformation of the self in her body of language, in the construction of provisory significations of poetic subjectivity through experiences of both the rupture of established notions of world and the subject translated in writing. We seek to comprehend how this poetic gesture implicates the contact with the unexpected, the inapprehensible aspects of poetical meaning, which is reflected in the subjective search and its own limits — especially when there are vacuums, silences that live in the acts of speech, unutterable, whose traces indicate that the subject inscribed in this space is an effect of the same act of incompleteness.